Foreign Ownership, Managerial Ownership, Profitability, Media Exposure and Intensity of Corporate Social Responsibility Disclosure - Ni Made Desi Ratnadewi; I Gde Ary Wirajaya (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
CSR disclosure is the disclosure of all information on social activities carried out by the company. The purpose of this study is to determine the effect of foreign ownership, managerial ownership, profitability, and media exposure on the intensity of CSR disclosure. This study uses a sampling method, namely non-probability sampling with purposive sampling technique. There are 173 companies with 519 observations. The data analysis technique used is multiple linear regression analysis. The results showed that profitability and media exposure had a positive effect on the intensity of corporate social responsibility disclosure. Managerial ownership has a negative effect on the intensity of corporate social responsibility disclosure. Foreign ownership has no effect on the intensity of corporate social responsibility disclosure.